2004
DOI: 10.4028/www.scientific.net/kem.264-268.449
|View full text |Cite
|
Sign up to set email alerts
|

Tribology of Advanced Ceramics and Hard Coatings

Abstract: Fine ceramics such as SiC, Si 3 N 4 and ZrO 2 and hard ceramic coatings such as DLC and CN x show attractive tribological properties of low friction and low wear in vacuum, air or water which cannot be observed with metals. Some typical observations are introduced and mechanisms are discussed in this paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The comparison of the tribological properties of the Cr 2 O 3 -based samples with the DLC, TiN, and TiAlN coatings and of the uncoated samples in contact with cast iron counterbodies found that the samples with the DLC coatings demonstrated the highest scuffing resistance and the lowest coefficient of friction (COF) [40]. The studies carried out in air and in water environment, in nitrogen atmosphere, and in vacuum revealed a significant decrease in the COF, an increase in wear and oxidation resistance after deposition of the DLC coatings on the substrates of SiC, Si 3 N 4 , and ZrO 2 [41,42]. Close values of the elastic modulus of the coating and the substrate is an important factor able to reduce internal stresses and thus improve the service life and reliability of products with the DLC coatings.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The comparison of the tribological properties of the Cr 2 O 3 -based samples with the DLC, TiN, and TiAlN coatings and of the uncoated samples in contact with cast iron counterbodies found that the samples with the DLC coatings demonstrated the highest scuffing resistance and the lowest coefficient of friction (COF) [40]. The studies carried out in air and in water environment, in nitrogen atmosphere, and in vacuum revealed a significant decrease in the COF, an increase in wear and oxidation resistance after deposition of the DLC coatings on the substrates of SiC, Si 3 N 4 , and ZrO 2 [41,42]. Close values of the elastic modulus of the coating and the substrate is an important factor able to reduce internal stresses and thus improve the service life and reliability of products with the DLC coatings.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Zirconia (ZrO 2 ) as important ceramic coating material, endows excellent physical properties such as high-temperature resistance, wear resistance and corrosion resistance, rendering it widely applied as refractory materials and ceramic pigments [1,2]; additionally, it has received greatly increasing interest in the high-tech fields of bio-ceramics, electronic ceramics, functional ceramics and structural ceramics, etc., [3][4][5][6]. However, during the heating and cooling process, undoped pure zirconia with polymorphism is accompanied by volume expansion, and this volume expansion exceeds the elastic limit of zirconia [7].…”
Section: Introductionmentioning
confidence: 99%
“…Partially stabilized zirconia (PSZ) ceramics materials present excellent physical properties, including reasonable chemical inertness, low thermal conductivity, strong corrosion resistance, small thermal expansion coefficient, and excellent thermal shock resistance [1][2][3]. Therefore they are expected to gradually replace the widespread applications of pure zirconia (ZrO 2 ) in advanced ceramics materials, for instance, electronic ceramics, functional ceramics, bio-ceramics, and structural ceramics [4][5][6].…”
Section: Introductionmentioning
confidence: 99%